The effect of transformational leadership in the employee’s motivation in the organizations - محمد علي, عالية جواد (Journal of Economics and Administrative Sciences, 2012)
The transformational leaderships in all organizations  consider Motivations policies which is one of the main and basic policies adapted by the successful leaderships in all organizations, in order to be able to achieve essential goals, such as enhancing loyalty of employees towards their organizations and also developing and empowering their capacities and abilities in work, leading to development and increasing productivity and reducing production costs to the minimum, then reaching immense profits and benefits, in addition to development of excellence in the market of competition. The research was performed in the (General Company of Leather Industries/ in Baghdad ,in alkarada) the study reached to many of results such as ignoring motivations policies by the higher leadership of the organization, leading to creating weariness and annoyance in work, while using various motivation policies in different events and in accordance with efforts performed by employees in work, will increase loyalty towards organization in addition to continuing developing their capacities and abilities to achieve better organization level